The Chinese traditional garden and its influence on Western gardens - Li, Su (SLU/Landscape Architecture (until 121231), 2012)
This paper has two aims. The first is to explicate Chinese traditional gardening and landscape theory and to give a more in-depth analysis of Western landscape thoughts, garden creation ideas, landscape development, landscape layout, gardening factors and enlightenment in order to acquire an objective understanding of how Chinese’s classical landscape might have influenced the ideas of Western landscape and gardens. Therefore, I will explore how Chinese garden ideals might have influenced, with a particular focus on the period of the enlightenment and the romantic era, the development of the "informal," "romantic," "natural," "landscape" garden in the Europe. The second aim is to relate traditional gardening and landscape theory to contemporary concepts, such as that of place, which are of importance to urban and regional planning. This thesis focuses on following questions: - Why has Chinese landscape design attracted attention for such a long period of time? Is it possible to comprehend how Chinese culture differs from other countries culture and if so how has it drawn attention elsewhere the world? In order to try to answer these questions, I will compare and discuss the developmental course of both the European landscape gardens and Chinese traditional gardens according to different historical process. The Chinese traditional garden, beginning with its primitive form, has gone through various periods and dynasties, finally forming its unique style, and it has later been welcomed by many western countries. Its special characteristics and ideas will be the key of discussion, which may be the answer to the question raised previously. Since the Renaissance period, European countries have undergone a series of cultural and economic changes. The idea of gardening has also gradually improved and absorbed new gardening ideas from other countries and cultures. Different countries have different ways of gardening but there has also been interaction between them. At the 6 time Chinese culture came into Europe we can discern that the Chinese elements have been applied in the different types of European gardens. There is evidence that the appearance of Chinese elements and ideas changed the European idea of gardening, paving the way for the landscape gardens. Here, I will seek to explain how the Chinese traditional garden might have influenced the European landscape garden.